The Novel Wheat Transcription Factor TaNAC47 Enhances Multiple Abiotic Stress Tolerances in Transgenic Plants - Zhang, Lina; Zhang, Lichao; Xia, Chuan; Zhao, Guangyao; Jia, Jizeng; Kong, Xiuying (Frontiers in Plant Science, 2016)
NAC transcription factors play diverse roles in plant development and responses to abiotic stresses. However, the biological roles of NAC family members in wheat are not well understood. Here, we reported the isolation and functional characterization of a novel wheat TaNAC47 gene. TaNAC47 encoded protein, localizing in the nucleus, is able to bind to the ABRE cis-element and transactivate transcription in yeast, suggesting that it likely functions as a transcriptional activator. We also showed that TaNAC47 is differentially expressed in different tissues, and its expression was induced by the stress treatments of salt, cold, polyethylene glycol (PEG) and exogenous abscisic acid (ABA). Furthermore, overexpression of TaNAC47 in Arabidopsis resulted in ABA hypersensitivity and enhancing tolerance of transgenic plants to drought, salt and freezing stresses. Strikingly, overexpression of TaNAC47 was found to activate the expression of downstream genes and change several physiological indices that may enable transgenic plants to overcome unfavorable environments. Taken together, these results uncovered an important role of wheat TaNAC47 gene in response to ABA and abiotic stresses.